Problems of Creativity Development Methodology in Educational Practice - Bogoyavlenskaya, D.B. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2023)
The article reflects the contradictions that characterize the current state of Russian education system. It is believed that the abolition of the Bologna system of education will contribute to the restoration of its former high level. However, the material we have cited from a survey of leading teachers points to deeper reasons for its decline. First of all, it should be noted the orientation towards the introduction into pedagogy of a system of basic indicators of child development seen as a partof the dominant American concept of behaviorism, which explains the development of the cognitive process and creativity tvorchestvo - in Russianonly by an associative process. Studies, presentations at the conferences, and a survey the author conducted among Russian teachers show that, assuming a higher role in the development of "creativity" than in the development of tvorchestvo or "creative skills", teachers actually form among students a significant attitude towards creativity . The concepts of tvorchestvo and "creativity", unfortunately, are considered the same thing in in the scientific world. Confusing these concepts, a professional Russian teacher contradicts the scientifically based Russian methodology, which is a decisive factor in the development of education in Russia. В статье отражены противоречия, характеризующие современное состояние отечественной системы образования. Считается, что отмена Болонской системы образования позволит способствовать восстановлению прежнего высокого ее уровня. Однако приведенный нами материал опроса передовых учителей указывает на более глубинные причины ее упадка. В первую очередь, следует отметить ориентацию на внедрение в педагогику системы основных показателей развития ребенка, разработанных в доминирующей в Америке концепции бихевиоризма, сводящего развитие познавательного процесса и творчества (креативности) лишь к ассоциативному процессу. Примеры отождествления учителями понятий творчества и креативности (по Дж. Гилфорду) в докладах на ряде конференций и по результатам проведенного автором опроса демонстрируют, что, предполагая более высокую роль в развитии «креативности», чем «творческие способности», педагоги фактически формируют у школьников значимое отношение к этому понятию. Наивно веря в тождественность понятий «творчество» и «креативность», что, к сожалению, усиливает уже сложившаяся традиция и в научном мире, профессиональный педагог фактически противоречит научно обоснованной отечественной методологии как решающего фактора развития российского образования.